HORIZONTAL DISPERSAL AND CLIMBING BEHAVIOUR OF THE CAMEL TICK HYALOMMA DROMEDARII (ACARI: IXODIDAE) IN DESERT ECOSYSTEM OF NORTHERN SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
Thirty adults of Hyalomma dromedarii were released in grass arenas. Dispersal distances of the recaptured ticks were measured every other day for 14 days. Similarly, 5000 larvae and 50 adults of the same tick species were released in each of five metal arenas containing vertically erected sticks. Their diurnal climbing heights were measured at 0600, 1200 and 1800 hours for three successive days. Dispersal of adults in grass ranged between 41 and 144 cm.  Adults had no tendency of climbing vegetation. Larvae climbed on the second day for maximum heights of 28.9 and 34.4 cm. They preferred to climb in the afternoon hours to reach maximum heights that ranged between 37.9 and 50.3 cm.